ORGANIZATION AND MANAGEMENT OF EDUCATION AND TRAINING PROCESSES BASED ON MODERN PRODUCTION TECHNOLOGIES - Jamshid Shamshidinovich Kazimov (Galaxy International Interdisciplinary Research Journal, 2023)
In the developed countries of the world, the educational policy aimed at meeting the socio-economic needs of the individual, the state and the society, in order to educate a well-rounded and well-rounded person, instills the need for students to acquire knowledge and thoroughly master the news, the basic academic-scientific, general cultural knowledge, spiritual and moral qualities based on national and universal values. , implies the formation and development of skills of creative thinking, conscious attitude to the environment. From this point of view, it is urgent to develop and improve mechanisms for ensuring the consistency, integrity and continuity of educational processes and innovative technologies that serve to increase the effectiveness of this process in the training of highly qualified and competitive personnel.